The Relationship Between Tobacco Smoking, Cortisol Secretion, and Sleep Continuity. (24th August 2019) - Cohen, Ami; Colodner, Raul; Masalha, Rifat; Haimov, Iris
Abstract: Background : Existing theories hold that chronic tobacco smoking leads to the development of adverse psychological symptoms, thus producing a compulsive urge to smoke in order to alleviate these sensations. Sleep disturbances are often considered among the negative consequences of chronic smoking. Objectives : The current study aimed at examining whether dysregulation of the hypothalamic-pituitary-adrenocortical (HPA) axis may be involved in this disruption of sleep quality among smokers. Methods : Smokers and non-smokers provided saliva samples following awakening for assessment of cortisol concentrations as a measure of HPA activity. Subsequently the participants completed the State-Trait Anxiety Inventory, Brief Questionnaire on Smoking Urges, the Fagerstrom Test for Nicotine Dependence, and the Pittsburgh Sleep Quality Index. Next, their sleep was monitored objectively for one week using an actigraph. Results : While smokers' self-reported sleep quality was similar to that of non-smokers, their sleep recording data pointed to diminished sleep continuity (increased wake time after sleep onset; WASO), while total sleep time and sleep onset latency were similar to that of non-smokers. Cortisol secretion was higher among smokers. However, among smokers only, cortisol was negatively correlated with WASO, suggesting that the direct enhancing effect of smoking on WASO is somewhat balanced by an indirect process related to higher cortisol levels. Possible interpretations for this inconsistent mediation are discussed. Conclusions/Importance : Smoking is associated with reduced sleep continuity and the relationship between smoking and sleep continuity may involve the HPA axis.